2009
DOI: 10.1111/j.1742-1241.2008.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Dying in an acute hospital setting: the challenges and solutions

Abstract: Summary More than half of all UK deaths occur in hospital, yet evidence suggests that the quality of inpatient end of life care is suboptimal at best. Over half of all NHS complaints pertain to problems with care in the dying phase, particularly with regard to poor communication. This is a hugely topical area following the recent publication of the Department of Health’s End of Life Care Strategy. With reference to current literature, we seek to investigate the challenges associated with providing ‘a good deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
101
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 29 publications
0
101
0
2
Order By: Relevance
“…Acute-care hospitals are thus a common place of death internationally; however they are generally fast-paced, high-tech environments, with care of the dying neither a primary focus nor prioritized (Bloomer, Endacott, O’Connor, & Cross, 2013; Chan, Macdonald, Carnevale, & Cohen, 2017). Several researchers point to deficits in quality end-of-life (EoL) care in acute-care hospitals (Al-Qurainy, Collis, & Feuer, 2009; Oliver & O’Connor, 2015; Reyniers, Houttekier, Cohen, Pasman, & Deliens, 2014), with both organizational and environmental factors contributing to a lack of support for dying persons and their family members (Sheward, Clark, Marshall, & Allan, 2011; Virdun, Luckett, Lorenz, Davidson, & Phillips, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Acute-care hospitals are thus a common place of death internationally; however they are generally fast-paced, high-tech environments, with care of the dying neither a primary focus nor prioritized (Bloomer, Endacott, O’Connor, & Cross, 2013; Chan, Macdonald, Carnevale, & Cohen, 2017). Several researchers point to deficits in quality end-of-life (EoL) care in acute-care hospitals (Al-Qurainy, Collis, & Feuer, 2009; Oliver & O’Connor, 2015; Reyniers, Houttekier, Cohen, Pasman, & Deliens, 2014), with both organizational and environmental factors contributing to a lack of support for dying persons and their family members (Sheward, Clark, Marshall, & Allan, 2011; Virdun, Luckett, Lorenz, Davidson, & Phillips, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…12,19,20 Despite the benefits of palliative care [18][19][20][21][22][23][24][25] and its growth in recent years, 20,25,27 it is not always available for inpatients, partly because the subspecialty palliative care workforce is not currently sufficient to reach all patients dying in hospital settings and partly because practitioners do not recognize shifts in patient trajectory indicating the need for palliative care consultation. [26][27][28][29][30][31][32] In an environment focusing on "cure," transition away from disease-modifying treatments to symptom control can seem counterintuitive. Because most Americans are likely to die in a hospital or nursing home, 20,33,34 there is a compelling need to address processes of care for actively dying patients in inpatient settings.…”
Section: Introductionmentioning
confidence: 99%
“…156,158 Research has found that such patients may welcome the opportunity for their voice to be included and to make a contribution to research that will benefit others in future. [159][160][161][162] Consequently, it has been argued that excluding vulnerable patients from the opportunity to take part in research on the basis of assumptions made about their experiences and preferences is discriminatory and restrictive. [163][164][165][166][167] However, we were well aware of the need to approach contacts with patients and family carers with the utmost care and sensitivity, and to be suitably responsive to patient and family carer reactions and preferences throughout the research.…”
Section: Ethical Issuesmentioning
confidence: 99%